URGENSI PENDAFTARAN HAK MEREK SEBAGAI BENTUK PERLINDUNGAN HUKUM BAGI PELAKU USAHA MIKRO KECIL DI BIDANG KULINER - Permata, Cindy; Fitriyani, Jeanny Anggita; Akbar, Sahda Saraswati; Yacub, Tifanny Nur; Gumilar, Egi Rivaldi; Safitri, Nadila; Sitanggang, Matthew Jakaria; Yulistio, Muhammad Raihan; Sabrina, Fadiah Tarisa; Falevi, Yunizar; Ningtyas, Meira Lalia Ayu; Purba, Rebecca; Roulina, Cahaya Grace; Amelia, Sandra; Fattah, Ade Syaifullah; Azza, Yaumil; Supardi, Reisha Rizkia Sabila; Setiawan, Felicia Stefanie; Sitorus, Christofel Adam; Juwita, Hana Rahmahdhani; Eriana , Nadhifa Putri; Reynita, Kayla Tiara (Zhata Institut, 2024)
The trade sector is one of the supports for the continuity of human life in increasing economic growth. The era of global trade is in line with international conventions that have been ratified by Indonesia so the role of brands is significant in maintaining healthy business competition. A brand becomes a marker that can be expected to produce economic value. Brands have an important role in describing a product's quality and commercial value, so it is necessary to apply for brand registration. However, according to the Directorate General of Intellectual Property (DJKI) of the Ministry of Law and Human Rights, there are still many MSME players who have not registered their brands, because MSME capital is still limited and there is a lack of understanding of the benefits of brand registration for the MSME industry. The observation method was used when searching for target partners, which in this activity was Kedai Geprek Mavera, an MSME in the culinary sector in the South Jakarta area. The activity was carried out in the form of socialization to MSME actors directly orally, covering the meaning of brand rights, the importance of registering a brand right, then the risks if the brand is not registered, as well as a simulation of registering the target partner's brand rights.